The Relationship Of Occupational Health And Safety Knowledge With The Work Attitude Of Culinary Students At Smk Negeri 6 Padang - Miranti, Meliza Wahyu; Yulastri, Asmar (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research is motivated by the knowledge of occupational health and safety (K3) students are still low, the application of K3 knowledge is still lacking and the work attitude of students who ignore K3 procedures during practicum in the laboratory. This study aims to: 1) describe the knowledge of K3; 2) describe students' work attitudes; and 3) analyzing the relationship between knowledge of K3 and work attitudes of culinary students at State 6 Padang Vocational High School (SMK). This type of research is quantitative with a correlational approach. The population of this research is the XII culinary students at SMK Negeri 6 Padang for the academic year 2020/2021 totaling 95 people. The sampling technique used is saturated sampling, where all members of the population are taken to samples. Data collection was carried out with test instruments and questionnaires via google form. The test instrument uses a system without fines and a questionnaire using a Likert scale. The test instrument has been tested for validity, reliability, index of difficulty and discriminating power of the question, while the validity and reliability of the questionnaire have been tested. Data were analyzed by descriptive and correlation analysis. The results showed that K3 knowledge overall in the moderate category with a percentage of 32%. The work attitude of students in the very high category with a percentage of 28%. The results of the correlation test can be concluded that there is a positive and significant relationship between K3 knowledge and the work attitude of culinary students at SMK Negeri 6 Padang with a value of tcount > ttable.